Economics, religion and happiness God, Mammon and the search for spiritual and financial wealth - Borooah, Vani K. 1947- (Routledge, Taylor & Francis Group, 2024)
Setting the Scene -- What Makes People Happy? -- Objective and Subjective Measures of Happiness -- Religious Hatred and Religion-Inspired Violence -- Income and Job Satisfaction -- Prejudice -- Conclusions.
Keywords: Glück; Wohlstand; Der Andere; Gutes Leben; Lebensqualität; Quality of life; Happiness / Economic aspects; Happiness / Religious aspects; Economics / Sociological aspects; BUSINESS & ECONOMICS / Economics / Theory; BUSINESS & ECONOMICS / Economic Conditions; BUSINESS & ECONOMICS / Development / Economic Development; Aufsatzsammlung